Evaluating the efficacy of nutrient solution reuse in hydroponics - Tetteh, Millicent (My University, 2025)
Nutrient solution reuse in hydroponics is a sustainable strategy to improve resource efficiency. However, increased microbial risks, nutrient toxicity, and accumulation of allelochemicals can compromise system safety and crop yield. The first objective of this study they are not specifically tailored to hydroponic nutrient solutions. This review synthesizes current knowledge on the risks and opportunities of nutrient reuse in hydroponic systems, highlighting emerging treatment technologies and the urgent need for hydroponics-specific, science-based standards to ensure both sustainability and food safety to support production by small scale farmers. In the second objective, we evaluated the combined performance of slow sand filtration (SSF), biochar filtration, and UV-C disinfection for multi-cycle reuse of hydroponic nutrient solution in romaine lettuce production and assessed the impact of treated nutrient solutions use of plant growth and nutritional quality. Results showed that SU (SSF + UV-C) and SBU (SSF + Biochar + UV-C) consistently achieved ≥5 log₁₀ reductions of E. coli, meeting World Health Organization (WHO) microbial safety criteria. Physically, turbidity remained <2 NTU, and SBU showed the highest light transmittance. Chemically, both treatments reduced ammonium-N, total N, and total P, with SBU showing the highest removals. However, nitrate levels remained relatively stable, calcium steadily accumulated across cycles, and pH in SU and C fell below Food and Agriculture Organization (FAO)/World Health Organization (WHO) guidelines. Micronutrient analysis revealed substantial declines in Fe, Zn, Cu, and Mn—up to 90–97% in SBU resulting in progressive micronutrient imbalance despite EC-based nutrient supplementation. Romaine lettuce grown in SU initially produced the highest biomass but declined by ~30% across cycles, while SBU showed even larger reductions (~45%). Chlorophyll, SPAD, and vitamin C decreased in all treatments, reflecting micronutrient depletion, salinity stress, and oxidative damage. The freshwater treatment also experienced reduced quality due to ammonium accumulation. Overall, combining SSF, biochar, and UV-C provides effective microbial inactivation and maintains physical water quality but progressively depletes essential micronutrients, limiting long-term crop performance. These findings highlight the potential of low-cost treatment systems for small-scale hydroponic growers while emphasizing the need for cycle-specific micronutrient supplementation to sustain yield and nutritional quality during extended nutrient-solution reuse.
Keywords: Small scale hydroponics; Nutrient reuse; UV-C disinfection; Deep water culture system; Romaine lettuce; Treatment